How does tax avoidance affect transparency? - LI, Congcong (Institutional Knowledge at Singapore Management University, 2018)
This study examines how tax avoidance affects corporate transparency. Using a large sample ofU.S. firms from 1995 to 2016, we find a significant non-linear effect of tax avoidance ontransparency. That is, when a firm’s tax avoidance is low, an increase in tax avoidance improvestransparency; however, when a firm’s tax avoidance is high, an increase in tax avoidance decreasestransparency. These results are robust to using alternative measures of transparency and taxavoidance and in several additional tests. Overall, the findings suggest that the effect of taxavoidance on transparency depends on the aggressiveness of firms’ tax avoidance behavior. Ourstudy contributes to the literature on the economic consequences of tax avoidance.